The Neutralizing Antibody Response to the HIV-1 Env Protein - Moore, Penny L. (Current HIV Research, 2018)
Background: A vaccine able to elicit broadly neutralizing antibodies capable of blocking infection by global viruses has not been achieved, and remains a key public health challenge. Objective: During infection, a robust strain-specific neutralizing response develops in most people, but only a subset of infected people develop broadly neutralizing antibodies. Understanding how and why these broadly neutralizing antibodies develop has been a focus of the HIV-1 vaccine field for many years, and has generated extraordinary insights into the neutralizing response to HIV-1 infection. Results: This review describes the features, targets and developmental pathways of early strainspecific antibodies and later broadly neutralizing antibodies, and explores the reasons such broad antibodies are not more commonly elicited during infection. Conclusion: The insights from these studies have been harnessed for the development of pioneering new vaccine approaches that seek to drive B cell maturation towards breadth. Overall, this review describes how findings from infected donors have impacted on active and passive immunization approaches that seek to prevent HIV-1 infection.
Keywords: passive immunity